Anti-microbial and anti-inflammatory activities of crude and acidified fraction of selected Malaysian honey samples - Mohd. Ismail, Nurul Izzati (2015)
Honey has been reported to have anti-microbial and anti-inflammatory properties, due to the presence of polyphenol and hydrogen peroxide, respectively. To our knowledge, the detail compounds that contribute to the activities are still unknown. Therefore, this study was focused on anti-microbial and the anti-inflammation activities of selected honey samples including Tualang, Acacia and Gelam honey from Malaysia. First, the honey samples were fractionated by acidified water (pH 2) in a solid phase extractor using C18 column. Then, the honey fraction was assayed for anti-microbial and anti-inflammatory activities using well diffusion method and enzymatic cyclooxygenase (COX-1 and -2) assay, respectively. For antimicrobial study, four different microbial strains consisted of gram positive (Staphylococcus aureus) and gram negative (Salmonella typimurium) bacteria, yeast (Candida albican), as well as fungi (Fusarium oxysporum) were tested on the honey samples. The result showed that only Salmonella typimurium and Candida albican were inhibited by crude and acidified fraction of Tualang, Acacia and Gelam honey, but no inhibition was observed for Staphylococcus aureus and Fusarium oxysporum. The minimum inhibitory concentration (MICs) of the crude honey samples (50.0% w/v) and their fractions (12.5-25.0% w/v) against Salmonella typimurium were about two to three times higher than the MICs of Manuka honey and its fraction (6.3- 12.5% w/v). However, the MICs of honey samples (3.1-6.3% w/v for crude honey samples and 0.8-3.1% w/v for their acidified fractions) against Candida albican appeared to be better, or at least comparable to Manuka honey samples (25.0% w/v for crude honey samples and 3.1% w/v for their acidified fractions). On the other hand, the anti-inflammatory activity of honey samples at 50% of inhibition (IC50) was found to be 0.7-1.7 mg/µL for COX-1 and 0.4-1.3 mg/µL for COX-2. Fractionation did not improve the anti-inflammatory activity of honey samples because their IC50 values were increased to 320.0-1080.0 mg/L for COX-1 and 280.0-400.0 mg/L for COX-2. In term of selectivity ratio of COX-1/COX-2, the crude honey samples of Gelam (ratio=3.3) and its fraction (ratio=2.7) appeared to be the most selective COX-2 inhibitor, which was about two times higher than the selectivity of Manuka honey. The anti-microbial and anti-inflammatory properties of honey could be due to the presence of quercetin, chlorogenic acid, acacetin, apigenin-7-o-glucoside, myricetin and coumaryl quinic acid. These phenolic acids and flavonoids were detected in the honey fraction.